Understanding the suitable alloying conditions for highly efficient Cu- and Mn-doped Zn1-xCdxS/ZnS core-shell quantum dots - Kaur, Manpreet (2024)
Doping of alloyed colloidal quantum dots (QDs) has garnered significant attention for providing tunable and Stokes-shifted emission. By alloying the host semiconductor nanocrystals (NCs), their band gap can be tuned. With the specific addition of dopant ions, these NCs can emit tunable emissions within the visible spectrum. However, while doped and alloyed quantum dots (QDs) have shown promise for tunable emissions, their emission qualities have not been consistent across the spectrum. Here, we report the synthesis of high-quality Cu- and Mn-doped ZnxCd1-xS (x = 0–1) alloyed QDs by a colloidal non-injection method. In this study, we examined the effect of different dopant ions on the optical properties of similar alloyed nanocrystals. The deposition of a ZnS shell on these doped QDs significantly improves their quantum yield (QY), increasing it from 7.0 % to 50.0 % for Cu-doped QDs and from 30.0 % to 80.0 % for Mn-doped QDs. The Cu-doped QDs exhibit tunable emission from green to red across the visible spectrum by varying the Zn/Cd ratio, whereas the Mn-doped QDs show a fixed orange emission. Interestingly, the Cu-doped alloyed QDs show a contrasting trend in quantum yield (QY) compared to those of Mn-doped QDs when the amount of Cd in ZnCdS alloyed QDs is systematically changed. As the amount of Cd increases in the ZnCdS alloyed QDs, the Cu-doped QDs show both an increase in average lifetime and an increase in QY. In contrast, for the Mn-doped QDs, the decay lifetime values remain fairly constant for different amounts of Cd in the ZnCdS alloyed QDs, but the QY decreases as the amount of Cd increases. The results of this study may facilitate the design of optimal alloying combinations for Cu/Mn-doped QDs in optoelectronic applications.